Impact of ingredient selection on rheological properties of a semi-liquid syrup model for use in pulp/paste candy - Stangl, Kimberly (Kansas State University, 2016)
Pulp/paste candy is popular in Mexico and is gaining popularity around the world. Pulp/paste candy is characterized as a soft, semi-fluid candy with particles in a colloidal suspension, typically squeezed out of the package for consumption. It is made by hydrating gums in water and mixing them with corn syrup, acid, powdered/pulverized sugar, and other minor ingredients yielding a product around 80°Brix and pH between 2-3. Over time the sucrose in the candy tends to invert, causing two types of failure: package leakage and solidification in package. Based on the findings of previous work from Molina-Rubio et al. (2010), a modified semi-liquid syrup model system was created with corn syrup, sugar, gums, and water. The model system was used to identify the influence these ingredients had on viscosity and texture since these factors are linked to the typical modes of failure in pulp/paste candy. An oscillatory sweep was used on a controlled force rheometer to identify the linear viscoelastic range. Oneway ANOVA with Tukey HSD was used to compare % total solids levels with complex viscosity at 0.1 rad/sec (there was a significant difference between all levels) and minimum tan (delta) (mid and high level were similar). Using a stepwise method, ANOVA models were generated that showed statistically significant effects on complex viscosity for gum level and sugar level as well as interactions (p < 0.05) between invert syrup-water, gum-water, and sugar type-water. The type of gum and the amount of corn syrup used didn’t significantly impact on the viscosity of the system. Using probe tests helped to analyze samples that were too thick for the rheometer. Analysis showed an inflection point for exponentially increased hardness (85-93%TS) that should be further investigated. The stepwise regression model generated for stickiness showed that the invert syrup-water interaction was significant along with gum type. These results are applicable to the confectionery industry and can help companies test and create a candy that meets the packaging and shelf life constraints that they desire. Targeting invert syrup-water levels and the hydration of the gum will have the most impact on the final product’s viscosity and stickiness, which are important for primary package filling and storage. To create an easy to eat candy, no invert syrup should be used in formulation and gellan gum would be better to use than xanthan. Higher solids (> 85%) should also be avoided since it would create a candy that is harder to squeeze out of the package due to higher viscosity and textural hardness.
Keywords: Rheology; Pulp/Paste candy; Semi-liquid syrup model; Viscosity; Texture